2013
DOI: 10.1177/0148607113484066
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Nutrition in Improving Quality of Care

Abstract: The current era of healthcare delivery, with its focus on providing high-quality, affordable care, presents many challenges to hospital-based health professionals. The prevention and treatment of hospital malnutrition offer a tremendous opportunity to optimize the overall quality of patient care, improve clinical outcomes, and reduce costs. Unfortunately, malnutrition continues to go unrecognized and untreated in many hospitalized patients. This article represents a call to action from the interdisciplinary Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0
6

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 225 publications
(81 citation statements)
references
References 61 publications
1
66
0
6
Order By: Relevance
“…However, the clinical importance of adequate nutrition care and its impact on patient-centred care is recognized but not always acted upon [14, 15, 25, 26]. Raising awareness and providing education about the issue is important, but it is not enough.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the clinical importance of adequate nutrition care and its impact on patient-centred care is recognized but not always acted upon [14, 15, 25, 26]. Raising awareness and providing education about the issue is important, but it is not enough.…”
Section: Discussionmentioning
confidence: 99%
“…For improving nutrition care practices, dietitians cannot do this alone. Dietitians should work as part of an interdisciplinary team to effect beneficial changes in nutrition care for all patients [15]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As approximately 20%–50% of patients in acute care are malnourished [2,3] effective strategies to address this significant problem are needed. In 2013, the Alliance to Advance Patient Nutrition published a call to action for improving nutrition care in hospitals [7], which suggested that a comprehensive approach involving all staff was needed [2,8,9]. In response, a consensus based Integrated Nutrition Pathway for Acute Care (INPAC) was developed [10].…”
Section: Introductionmentioning
confidence: 99%
“…Classifications reflect distinctions inherent in the world, assume determinism (Polit & Beck, 2012), and facilitate predictions. Traditionally theories and scientific knowledge are produced within a discipline, until it was proven that interdisciplinary coercion provides a more sophisticated knowledge and allow a better understanding of complex reality (Kim 2000;Peter et al, 2011;Tappenden et al 2013;Tjora & Melby, 2013). Interdisciplinary health research is increasingly encouraged and is often a specific requirement for research grants worldwide (Clarke, Hawkins, Sadler, et al, 2012).…”
Section: Academic Levelmentioning
confidence: 99%